Optical and electrical optimization of all-perovskite pin type junction tandem solar cells - Soldera, Marcos Maximiliano (2020)
A definitive breakthrough of perovskite solar cells towards large scale industrialization is believed to be the demonstration of higher efficiencies than conventional silicon technology, suggesting the exploration of perovskite tandem cell configurations. Since high efficiency tandem solar cells require careful optimization of photoactive as well as contact and additional functional layers, we propose an optical-electrical model to obtain the optimum layer thicknesses and the attainable electrical output parameters of two-terminal perovskite-perovskite tandem solar cells. The optical model takes into account the coherent propagation of light through the layer stack comprising two perovskite semiconductors and the corresponding contact layers, while the electrical model assumes two series-connected analytical current/voltage equations for pin solar cells. This model allows to assess the impact of the main physical parameters on each perovskite layer without requiring the high specificity needed in more rigorous numerical simulations. Efficiencies above 34 % are predicted considering available perovskites with non-optimum bandgap and contact materials already proven in efficient laboratory solar cells. The requisite to attain such efficiencies is that recombination at the interfaces between the perovskite and contact materials is kept low in both bottom and top cells. Furthermore, within the assumption of non-optimum bandgaps of currently available perovskites, the simulation results suggest that efficiencies around 37 % are possible when adopting contact materials with smaller absorption, more adequate refraction indices, and lower resistivity.